Preparation method of lithium manganese iron phosphate composite material containing MXene coating layer
By using MXene cladding on lithium manganese iron phosphate material, the problems of poor conductivity and easy dissolution of manganese ions are solved, and higher electrochemical performance and longer cycle life are achieved.
Patent Information
- Application Number
- CN202411422248.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-02-18
AI Technical Summary
The existing lithium manganese iron phosphate materials have problems such as poor conductivity and easy dissolution of manganese ions, which affects their cycle life and stability.
The preparation method of lithium manganese iron phosphate composite material using MXene clad layer is coated on the outer surface of lithium manganese iron phosphate body material through ultrasonic treatment and electrostatic self-assembly technology.
It effectively improves the conductivity of the material, improves its electrochemical properties, and inhibits the dissolution of manganese ions, extends the cycle life and improves stability.
Smart Images

Figure CN119480950A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery positive electrode material preparation, and in particular to a method for preparing a lithium manganese iron phosphate composite material containing a MXene coating layer. Background Art
[0002] The existing positive electrode materials of lithium-ion batteries mainly include lithium cobalt oxide (LiCoO2), ternary materials (LiNi1-x-yCoxMnyO2), lithium manganese oxide (LiMn2O4) and lithium iron phosphate (LiFePO4). The olivine-type lithium iron manganese phosphate LiFexMn1-xPO4 (LFMP) material is based on the development of lithium iron phosphate (LiFePO4) and lithium manganese phosphate (LiMnPO4). The theoretical performance and specific capacity of the three are relatively similar (170mAh / g). By introducing manganese ions, the diffusion channel of lithium ions can be broadened to a certain extent. By utilizing the synergistic effect of the two, the energy density can be increased by more than 20% with the same capacity in theory. Due to the introduction of manganese, the performance of lithium iron manganese phosphate batteries is also better at low temperatures. Compared with lithium iron phosphate batteries, lithium iron manganese phosphate batteries have higher energy density, better stability, longer cycle life and high safety. At the same time, under the condition of abundant manganese resources in the world, its material cost can be reduced by 10% compared with lithium iron phosphate, which is more cost-effective.
[0003] However, while the introduction of manganese elements improves the defects of lithium manganese iron phosphate, it also leads to new problems such as poor conductivity and manganese dissolution affecting cycle life and stability. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a method for preparing a lithium iron manganese phosphate composite material containing a MXene coating layer, aiming to solve the problems of poor electrical conductivity and easy dissolution of manganese ions in the prior art lithium iron manganese phosphate materials.
[0005] One object of the present invention is to provide a method for preparing a lithium manganese iron phosphate composite material containing a MXene coating layer, the method comprising:
[0006] Dispersing manganese salt, iron salt, phosphate salt and lithium salt solutions within a certain concentration range and antioxidants in a dispersant, respectively, and mixing them in a certain order to obtain a mixed solution;
[0007] The mixed solution is subjected to ultrasonic treatment under a protective atmosphere to obtain a lithium manganese iron phosphate dispersion;
[0008] After the lithium manganese iron phosphate dispersion is separated into solid and liquid and washed with water, it is dried in an oven at a set temperature;
[0009] calcining the oven-dried lithium iron manganese phosphate solid and cooling it to room temperature to obtain a lithium iron manganese phosphate bulk material;
[0010] The lithium iron phosphate bulk material is made into a dispersion and uniformly mixed with a MXene dispersion. After adjusting the pH to a set value, the MXene is coated on the outer surface of the lithium iron phosphate bulk material under ultrasound, and then filtered and freeze-dried to obtain a lithium iron phosphate composite material containing a MXene coating layer.
[0011] Furthermore, in the method for preparing the lithium manganese iron phosphate composite material containing a MXene coating layer, in the step of uniformly dispersing a manganese salt, an iron salt, a phosphate salt and a lithium salt solution within a certain concentration range and an antioxidant in a dispersant respectively:
[0012] The manganese salt is one or more of manganese sulfate, manganese nitrate and manganese dioxide;
[0013] The iron salt is one or more of ferrous sulfate, ferrous chloride and ferrous phosphate;
[0014] The lithium salt is one or more selected from lithium carbonate, lithium hydroxide, lithium dihydrogen phosphate, and lithium oxalate;
[0015] The total mixed concentration of manganese ions and iron ions is 0.5 mol / L to 1.2 mol / L, and the concentration of the lithium salt solution is 2.5 mol / L to 3.6 mol / L.
[0016] Furthermore, in the method for preparing the lithium manganese iron phosphate composite material containing a MXene coating layer, the antioxidant is ascorbic acid;
[0017] Calculated by mass percentage, the added amount of the ascorbic acid is 5-10% of the mass of the lithium manganese iron phosphate composite material.
[0018] Furthermore, in the above-mentioned method for preparing the lithium manganese iron phosphate composite material containing a MXene coating layer, the dispersant is one or more of polyvinyl pyrrolidone, polyacrylic acid, sodium polyacrylate, polyacetimide, and sodium phosphate.
[0019] Furthermore, in the above-mentioned method for preparing the lithium manganese iron phosphate composite material containing a MXene coating layer, the ultrasonic treatment time is 1-3 hours, and the protective atmosphere is one of nitrogen and argon.
[0020] Furthermore, in the method for preparing the lithium manganese iron phosphate composite material containing a MXene coating layer, the drying temperature of the oven is 80-120°C.
[0021] Furthermore, in the method for preparing the lithium manganese iron phosphate composite material containing a MXene coating layer, the calcination temperature is 500-700° C. and the calcination time is 1.5-2 hours.
[0022] Furthermore, in the method for preparing the lithium manganese iron phosphate composite material containing a MXene coating layer, the pH value is adjusted to 7-9.
[0023] Another object of the present invention is to provide a lithium iron manganese phosphate composite material, which is prepared by the above-mentioned method for preparing a lithium iron manganese phosphate composite material containing a MXene coating layer;
[0024] The lithium manganese iron phosphate composite material includes lithium manganese iron phosphate and a MXene coating layer coated on the outer surface of the lithium manganese iron phosphate.
[0025] Another object of the present invention is to provide a lithium-ion battery comprising the above-mentioned lithium manganese iron phosphate composite material.
[0026] Compared with the prior art: the present invention uses sonochemical reaction under a protective atmosphere to ultrasonically and uniformly disperse and mix manganese salt, iron salt, phosphate salt and lithium salt materials, then uses calcination to obtain a lithium iron manganese phosphate body, and finally attaches the lithium iron manganese phosphate body to a two-dimensional transition metal carbonitride material MXene through electrostatic self-assembly to obtain a modified lithium iron manganese phosphate composite material and a MXene-coated lithium iron manganese phosphate composite material, wherein ultrasound can make the lithium iron manganese phosphate and MXene materials more evenly dispersed; the MXene coating layer can not only effectively improve the electrical conductivity of the material, thereby improving its electrochemical properties, but also inhibit the dissolution of manganese ions in the material. DETAILED DESCRIPTION
[0027] Figure 1 This is a flow chart of a method for preparing a lithium manganese iron phosphate composite material containing a MXene coating layer proposed in one embodiment of the present invention; DETAILED DESCRIPTION
[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0030] In addition, the term "and / or" as used herein includes any and all combinations of one or more related listed items. In the detailed description and claims, a list of items connected by the term "one of" may mean any of the listed items. For example, if items A and B are listed, the phrase "one of A and B" means only A or only B. In another example, if items A, B, and C are listed, the phrase "one of A, B, and C" means only A; only B; or only C. Item A may contain a single element or multiple elements. Item B may contain a single element or multiple elements. Item C may contain a single element or multiple elements. In the detailed description and claims, a list of items connected by the terms "at least one of", "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" or "at least one of A or B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" or "at least one of A, B, or C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0031] The present invention aims at the problem that the introduction of manganese element improves the defects of lithium manganese iron phosphate, but also leads to new problems such as poor conductivity, manganese dissolution affecting cycle life and stability. A method for preparing a lithium manganese iron phosphate composite material containing a MXene coating layer is proposed. Please refer to Figure 1 , wherein the method comprises:
[0032] Step S10, manganese salt, iron salt, phosphate salt and lithium salt solutions within a certain concentration range and an antioxidant are uniformly dispersed in a dispersant respectively, and mixed in a certain order to obtain a mixed solution.
[0033] Among them, the manganese salt is one or more of manganese sulfate, manganese nitrate, and manganese dioxide; the iron salt is one or more of ferrous sulfate, ferrous chloride, and ferrous phosphate; the lithium salt is one or more selected from lithium carbonate, lithium hydroxide, lithium dihydrogen phosphate, and lithium oxalate; the total mixed concentration of manganese ions and iron ions is 0.5 mol / L to 1.2 mol / L, and the concentration of lithium salt solution is 2.5 mol / L to 3.6 mol / L. Exemplarily, the manganese salt and the iron salt can be first prepared into a mixed solution; the phosphate salt and the lithium salt are prepared into a solution; then the mixed solution is mixed with the solution prepared with the phosphate salt and the lithium salt, and then a dispersant is added, and then an oxidant is added to the mixed solution.
[0034] Specifically, the antioxidant is ascorbic acid; calculated by mass percentage, the amount of ascorbic acid added is 5-10% of the mass of the lithium manganese iron phosphate composite material; the dispersant is one or more of polyvinyl pyrrolidone, polyacrylic acid, sodium polyacrylate, polyacetimide, and sodium phosphate, preferably, polyvinyl pyrrolidone and polyacrylic acid are used.
[0035] Step 11, subjecting the mixed solution to ultrasonic treatment under a protective atmosphere to obtain a lithium manganese iron phosphate dispersion.
[0036] The ultrasonic treatment time is 1-3 hours, and the protective atmosphere is one of nitrogen and argon.
[0037] Step S12, separating the lithium manganese iron phosphate dispersion into solid and liquid, washing with water, and then drying it in an oven at a set temperature.
[0038] The lithium iron phosphate dispersion is separated into solid and liquid and washed with water, and then dried in an oven at 80-120°C, for example, 80°C, 100°C and 120°C.
[0039] Step S13, calcining the oven-dried lithium iron phosphate solid, and cooling it to room temperature to obtain a lithium iron manganese phosphate bulk material.
[0040] The calcination temperature is 500-700° C., such as 500° C., 600° C. and 700° C., and the calcination time is 1.5-2 hours, such as 1.5 hours and 2 hours.
[0041] Step S14, preparing the lithium iron manganese phosphate bulk material into a dispersion and uniformly mixing it with the MXene dispersion, adjusting the pH to a set value, and then coating the outer surface of the lithium iron manganese phosphate bulk material with MXene under ultrasound, and then filtering and freeze-drying to obtain a lithium iron manganese phosphate composite material containing a MXene coating layer.
[0042] Among them, MXene is a two-dimensional transition metal carbonitride. Its chemical formula is M n+1 X n T x , M represents a transition metal, such as Ti, Zr, Cr; X represents carbon and / or nitrogen atoms, where Tx represents the surface group on the outermost exposed M layer, which is one or more of -F, -O, and -OH. This surface functional group has high electronegativity, which is conducive to the electrostatic self-assembly with lithium manganese iron phosphate materials to construct modified composite materials. Specifically, the pH value is adjusted to 7-9, and ultrasound can make the lithium manganese iron phosphate and MXene materials more evenly dispersed. The MXene coating layer can not only effectively improve the conductivity of the material, thereby improving its electrochemical performance, but also inhibit the dissolution of manganese ions in the material.
[0043] On the other hand, the present invention further provides a lithium iron manganese phosphate composite material, which is prepared by the above-mentioned method for preparing a lithium iron manganese phosphate composite material containing a MXene coating layer.
[0044] Another aspect of the present invention provides a lithium-ion battery, comprising the above-mentioned lithium manganese iron phosphate composite material.
[0045] In order to facilitate understanding of the present invention, several embodiments of the present invention are provided below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thorough and comprehensive.
[0046] Example 1
[0047] S1. Manganese sulfate monohydrate and ferrous sulfate heptahydrate are prepared into a 1.2 mol / L mixed solution at a molar ratio of 8:2 using laboratory-made deionized water; lithium dihydrogen phosphate is prepared into a solution with a concentration of 3.6 mol / L; then the manganese iron mixed solution and the lithium dihydrogen phosphate solution are mixed, and then a polyacrylic acid dispersant is added, and then 10% of ascorbic acid of the total mass of manganese iron lithium is added to the mixed solution to prevent ferrous ions from being oxidized.
[0048] S2. The mixed solution is subjected to ultrasonic treatment under a nitrogen atmosphere at an ultrasonic power of 500 W for 2 hours. After the ultrasonic treatment is completed, a lithium manganese iron phosphate dispersion is obtained.
[0049] S3. The lithium manganese iron phosphate dispersion was separated by centrifugation and washed with water, and the obtained solid was dried in an oven at 100° C. for 12 hours.
[0050] S4. The dried lithium manganese iron phosphate solid is calcined at 500° C. for 2 hours. After the calcination is completed, it is cooled to room temperature to obtain a lithium manganese iron phosphate bulk material.
[0051] S5. Prepare a dispersion of the lithium iron manganese phosphate bulk material and evenly mix it with the MXene dispersion, adjust the pH to 7, coat the MXene on the outer surface of the composite material under ultrasound, then filter, and freeze-dry at below -30°C to obtain a MXene-coated lithium iron manganese phosphate composite positive electrode material powder.
[0052] Example 2
[0053] S1. Manganese sulfate monohydrate and ferrous sulfate heptahydrate are prepared into a 0.8 mol / L mixed solution at a molar ratio of 8:2 using laboratory-made deionized water; lithium dihydrogen phosphate is prepared into a solution with a concentration of 3.2 mol / L; then the manganese iron mixed solution and the lithium dihydrogen phosphate solution are mixed, and then a polyacrylic acid dispersant is added, and then 10% of ascorbic acid of the total mass of manganese iron lithium is added to the mixed solution to prevent ferrous ions from being oxidized.
[0054] S2. The mixed solution is subjected to ultrasonic treatment under a nitrogen atmosphere at an ultrasonic power of 500 W for 2 hours. After the ultrasonic treatment is completed, a lithium manganese iron phosphate dispersion is obtained.
[0055] S3. The lithium manganese iron phosphate dispersion was separated by centrifugation and washed with water, and the obtained solid was dried in an oven at 100° C. for 12 hours.
[0056] S4. The dried lithium manganese iron phosphate solid is calcined at 500° C. for 2 hours. After the calcination is completed, it is cooled to room temperature to obtain a lithium manganese iron phosphate bulk material.
[0057] S5. Prepare a dispersion of the lithium iron manganese phosphate bulk material and evenly mix it with the MXene dispersion, adjust the pH to 7, coat the MXene on the outer surface of the composite material under ultrasound, then filter, and freeze-dry at below -30°C to obtain a MXene-coated lithium iron manganese phosphate composite positive electrode material powder.
[0058] Example 3
[0059] S1. Manganese sulfate and ferrous sulfate are prepared into a 0.5 mol / L mixed solution at a molar ratio of 8:2 using laboratory-made deionized water; lithium dihydrogen phosphate is prepared into a solution with a concentration of 2.5 mol / L; then the manganese iron mixed solution and the lithium dihydrogen phosphate solution are mixed, and then a polyacrylic acid dispersant is added, and then 10% of ascorbic acid of the total mass of manganese iron lithium is added to the mixed solution to prevent ferrous ions from being oxidized.
[0060] S2. The mixed solution is subjected to ultrasonic treatment under a nitrogen atmosphere at an ultrasonic power of 500 W for 2 hours. After the ultrasonic treatment is completed, a lithium manganese iron phosphate dispersion is obtained.
[0061] S3. The lithium manganese iron phosphate dispersion was separated by centrifugation and washed with water, and the obtained solid was dried in an oven at 100° C. for 12 hours.
[0062] S4. The dried lithium manganese iron phosphate solid is calcined at 500° C. for 2 hours. After the calcination is completed, it is cooled to room temperature to obtain a lithium manganese iron phosphate bulk material.
[0063] S5. Prepare a dispersion of the lithium iron manganese phosphate bulk material and evenly mix it with the MXene dispersion, adjust the pH to 7, coat the MXene on the outer surface of the composite material under ultrasound, then filter, and freeze-dry at below -30°C to obtain a MXene-coated lithium iron manganese phosphate composite positive electrode material powder.
[0064] Example 4
[0065] S1 used laboratory-made deionized water to prepare a 1.2 mol / L mixed solution of manganese sulfate monohydrate and ferrous sulfate heptahydrate at a molar ratio of 8:2; lithium dihydrogen phosphate was prepared into a solution with a concentration of 3.6 mol / L; then the manganese iron mixed solution and the lithium dihydrogen phosphate solution were mixed, and then a polyacrylic acid dispersant was added, and then 10% of ascorbic acid of the total mass of manganese iron lithium was added to the mixed solution to prevent the ferrous ions from being oxidized.
[0066] S2: ultrasonically treating the mixed solution under a nitrogen atmosphere with an ultrasonic power of 500 W for 3 hours. After the ultrasonic treatment is completed, a lithium manganese iron phosphate dispersion is obtained.
[0067] S3: The lithium manganese iron phosphate dispersion is separated by centrifugation and washed with water, and the obtained solid is dried in an oven at 100° C. for 12 hours.
[0068] S4: calcining the dried lithium manganese iron phosphate solid at 500° C. for 2 hours. After the calcination is completed, cooling it to room temperature to obtain the lithium manganese iron phosphate bulk material.
[0069] S5 prepares a dispersion of lithium iron manganese phosphate bulk material and uniformly mixes it with a MXene dispersion, adjusts the pH to 7, coats the outer surface of the composite material with MXene under ultrasound, and then filters and freeze-dries it at below -30°C to obtain a MXene-coated lithium iron manganese phosphate composite positive electrode material powder.
[0070] Example 5
[0071] S1 used laboratory-made deionized water to prepare a 1.2 mol / L mixed solution of manganese sulfate monohydrate and ferrous sulfate heptahydrate at a molar ratio of 8:2; lithium dihydrogen phosphate was prepared into a solution with a concentration of 3.6 mol / L; then the manganese iron mixed solution and the lithium dihydrogen phosphate solution were mixed, and then a polyacrylic acid dispersant was added, and then 10% of ascorbic acid of the total mass of manganese iron lithium was added to the mixed solution to prevent the ferrous ions from being oxidized.
[0072] S2: ultrasonically treating the mixed solution under a nitrogen atmosphere with an ultrasonic power of 500 W for 1 hour. After the ultrasonic treatment is completed, a lithium manganese iron phosphate dispersion is obtained.
[0073] S3: The lithium manganese iron phosphate dispersion is separated by centrifugation and washed with water, and the obtained solid is dried in an oven at 100° C. for 12 hours.
[0074] S4: calcining the dried lithium manganese iron phosphate solid at 500° C. for 2 hours. After the calcination is completed, cooling it to room temperature to obtain the lithium manganese iron phosphate bulk material.
[0075] S5 prepares a dispersion of lithium iron manganese phosphate bulk material and uniformly mixes it with a MXene dispersion, adjusts the pH to 7, coats the outer surface of the composite material with MXene under ultrasound, and then filters and freeze-dries it at below -30°C to obtain a MXene-coated lithium iron manganese phosphate composite positive electrode material powder.
[0076] In order to further illustrate the embodiments of the present invention, the present invention also proposes corresponding proportions.
[0077] Comparative Example 1
[0078] The MXene-coated lithium manganese iron phosphate composite material and the preparation method thereof provided in this comparative example are basically the same as those in Example 1, except that ultrasonic treatment is not performed in step S2, but is replaced by conventional magnetic stirring.
[0079] Please refer to the following Table 1, which shows the preparation parameters corresponding to the above-mentioned Examples 1-5 and Comparative Example 1 of the present invention. It should be noted that in order to ensure the accuracy of the experiment, the preparation parameters should be the same except for the above-mentioned parameters.
[0080] Table 1
[0081]
[0082] In addition, the specific capacity of the positive electrode materials prepared in Examples 1-5 and Comparative Example 1 at 0.1C first discharge and 5C discharge specific capacity were tested to obtain corresponding performance parameters. The test results are shown in Table 2.
[0083] Table 2
[0084]
[0085] It can be clearly seen that the present application uses sonochemical reaction under a protective atmosphere to ultrasonically and evenly disperse and mix manganese salt, iron salt, phosphate salt and lithium salt materials, and then uses calcination to obtain the lithium iron manganese phosphate body, and finally attaches the lithium iron manganese phosphate body to the two-dimensional transition metal carbonitride material MXene through electrostatic self-assembly to obtain a modified lithium iron manganese phosphate composite material and a MXene-coated lithium iron manganese phosphate composite material, wherein ultrasound can make the lithium iron manganese phosphate and MXene materials more evenly dispersed; the MXene coating layer can not only effectively improve the electrical conductivity of the material, thereby improving its electrochemical properties.
[0086] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a lithium manganese iron phosphate composite material containing a MXene coating layer, characterized in that: The method comprises: Dispersing manganese salt, iron salt, phosphate salt and lithium salt solutions within a certain concentration range and antioxidants in a dispersant, respectively, and mixing them in a certain order to obtain a mixed solution; The mixed solution is subjected to ultrasonic treatment under a protective atmosphere to obtain a lithium manganese iron phosphate dispersion; After the lithium manganese iron phosphate dispersion is separated into solid and liquid and washed with water, it is dried in an oven at a set temperature; calcining the oven-dried lithium iron manganese phosphate solid and cooling it to room temperature to obtain a lithium iron manganese phosphate bulk material; The lithium iron phosphate bulk material is made into a dispersion and uniformly mixed with a MXene dispersion. After adjusting the pH to a set value, the MXene is coated on the outer surface of the lithium iron phosphate bulk material under ultrasound, and then filtered and freeze-dried to obtain a lithium iron phosphate composite material containing a MXene coating layer.
2. The method for preparing a lithium manganese iron phosphate composite material containing a MXene coating layer according to claim 1, characterized in that: In the step of uniformly dispersing a certain concentration range of manganese salt, iron salt, phosphate salt and lithium salt solution and an antioxidant in a dispersant respectively: The manganese salt is one or more of manganese sulfate, manganese nitrate and manganese dioxide; The iron salt is one or more of ferrous sulfate, ferrous chloride and ferrous phosphate; The lithium salt is one or more selected from lithium carbonate, lithium hydroxide, lithium dihydrogen phosphate, and lithium oxalate; The total mixed concentration of manganese ions and iron ions is 0.5 mol / L to 1.2 mol / L, and the concentration of the lithium salt solution is 2.5 mol / L to 3.6 mol / L.
3. The method for preparing a lithium manganese iron phosphate composite material containing a MXene coating layer according to claim 1, characterized in that: The antioxidant is ascorbic acid; Calculated by mass percentage, the added amount of the ascorbic acid is 5-10% of the mass of the lithium manganese iron phosphate composite material.
4. The method for preparing a lithium manganese iron phosphate composite material containing a MXene coating layer according to claim 1, characterized in that: The dispersant is one or more of polyvinyl pyrrolidone, polyacrylic acid, sodium polyacrylate, polyacetimide and sodium phosphate.
5. The method for preparing a lithium manganese iron phosphate composite material containing a MXene coating layer according to claim 1, characterized in that: The ultrasonic treatment time is 1-3 hours, and the protective atmosphere is one of nitrogen and argon.
6. The method for preparing a lithium manganese iron phosphate composite material containing a MXene coating layer according to claim 1, characterized in that: The drying temperature of the oven is 80-120°C.
7. The method for preparing a lithium manganese iron phosphate composite material containing a MXene coating layer according to claim 1, characterized in that: The calcination temperature is 500-700°C and the calcination time is 1.5-2 hours.
8. The method for preparing a lithium manganese iron phosphate composite material containing a MXene coating layer according to claim 1, characterized in that: Adjust pH to 7-9.
9. A lithium manganese iron phosphate composite material, characterized in that: It is prepared by the method for preparing a lithium manganese iron phosphate composite material containing a MXene coating layer as described in any one of claims 1 to 8; The lithium manganese iron phosphate composite material includes lithium manganese iron phosphate and a MXene coating layer coated on the outer surface of the lithium manganese iron phosphate.
10. A lithium ion battery, characterized in that: Including the lithium manganese iron phosphate composite material as described in claim 9.
Citation Information
Cited By
Lithium iron phosphate positive electrode material for lithium ion battery and preparation method of lithium iron phosphate positive electrode material
CN120191910A
Double-coated lithium iron manganese phosphate positive electrode material as well as preparation method and application thereof
CN121269662A
A double-coated lithium manganese iron phosphate positive electrode material, a preparation method and application thereof
CN121269662B